2017
DOI: 10.1186/s12958-016-0221-6
|View full text |Cite
|
Sign up to set email alerts
|

Induction of altered gene expression profiles in cultured bovine granulosa cells at high cell density

Abstract: BackgroundIn previous studies it has been shown that bovine granulosa cells (GC) cultured at a high plating density dramatically change their physiological and molecular characteristics, thus resembling an early stage of luteinization. During the present study, these specific effects on the GC transcriptome were comprehensively analysed to clarify the underlying mechanisms.MethodsGC were cultured in serum free medium with FSH and IGF-1 stimulation at different initial plating density. The estradiol and progest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 78 publications
(95 reference statements)
2
11
0
Order By: Relevance
“…p > 0.05, two-tailed Student's t -test. This figure is reproduced from Baufeld et al 15 . Please click here to view a larger version of this figure.…”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…p > 0.05, two-tailed Student's t -test. This figure is reproduced from Baufeld et al 15 . Please click here to view a larger version of this figure.…”
Section: Representative Resultsmentioning
confidence: 99%
“…To determine the transcript abundance, synthesize cDNA and measure specific transcripts by quantitative real-time polymerase chain reaction (qPCR) techniques 15 . A statistical evaluation should include at least three replications of different cell cultures, originated from different cell preparations (biological replicates).…”
Section: Protocolmentioning
confidence: 99%
“…In ovarian tissue and granulosa cells expression of specific subunits of the NMDA receptor, the subunits 1 and 2B, had been identified [ 50 ] thus supporting the view that this receptor might be involved in these cells as well. Expression of NMDAR subunits, especially of GRIN2D and GRINA has been found in vivo in GC (see database GranulosaIMAGE [ 51 ]) as well as in vitro (own GC culture microarray dataset [ 14 ]). Whether these receptor subunits can actually form functional receptors to be modulated by L-lactate in bovine GC has to be investigated in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, we showed that high cell density induces specific changes of the gene expression and steroid hormone profiles in cultured GC mimicking an early post-LH status of GC differentiation [ 13 ]. Furthermore, applying a whole-genome approach we could demonstrate in GC cultured at high plating density, that genes connected to hypoxia are affected [ 14 ]. In particular LDHA transcripts encoding L-lactate dehydrogenase were remarkably up-regulated.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, pathway enrichment analysis was performed using the Ingenuity Pathway Analysis (IPA) tool. P values were calculated using Fisher's exact test, and P values <0.05 were considered significantly enriched in the canonical pathways [ 11 ].…”
Section: Methodsmentioning
confidence: 99%